2023
DOI: 10.1091/mbc.e22-08-0326
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the binucleate ciliate Tetrahymena thermophila with asynchronous nuclear cell cycles

Abstract: Tetrahymena thermophila harbors two functionally and physically distinct nuclei within a shared cytoplasm. During vegetative growth, the ‘cell cycles’ of the diploid micronucleus and polyploid macronucleus are offset. Micronuclear S phase initiates just before cytokinesis and is completed in daughter cells prior to onset of macronuclear DNA replication. Mitotic micronuclear division occurs mid-cell cycle, while macronuclear amitosis is coupled to cell division. Here we report the first RNA-seq cell cycle analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Among the nine genes analyzed, one was designated as encoding hypothetical proteins, three lacked GO terms and the remaining five were identified as the genes associated with intracellular anatomical structure, translation, protein folding, membrane transport and electron transfer. To observe gene expression patterns of cells in each cell cycle, we scored cells based on the genes that had been previously reported as cell cycle-dependent (Zhang et al, 2023) and mapped on UMAP (Fig. 3 (a)).…”
Section: Clustering Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the nine genes analyzed, one was designated as encoding hypothetical proteins, three lacked GO terms and the remaining five were identified as the genes associated with intracellular anatomical structure, translation, protein folding, membrane transport and electron transfer. To observe gene expression patterns of cells in each cell cycle, we scored cells based on the genes that had been previously reported as cell cycle-dependent (Zhang et al, 2023) and mapped on UMAP (Fig. 3 (a)).…”
Section: Clustering Resultsmentioning
confidence: 99%
“…Seurat. The markers of each cell phase (Table S2) are based on the list from Zhang et al (2023). This score was then used to regress out the effect of the cell phase.…”
Section: Cell Cycle Scoring and Regressing Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Like all ciliated protozoa, T. thermophila harbors two functionally distinct nuclei within its cytoplasm: the transcriptionally silent, diploid ‘germline’ micronucleus and the transcriptionally active, polyploid ‘somatic’ macronucleus (reviewed in [ 11 ]). ORC-dependent DNA replication is coordinately regulated in vegetative growing Tetrahymena , such that the heterochromatic micronucleus and euchromatic macronucleus replicate their chromosomes at non-overlapping stages of the cell cycle (reviewed in [ 12 , 13 ]). Development is much more complex: multiple rounds of micro- and macronuclear DNA replication, meiosis, and mitosis occur in parental gametes and post-zygotic progeny.…”
Section: Introductionmentioning
confidence: 99%
“…While HHT3 (H3.3) is constitutively expressed in growing and starved cells [40,41], HHT4 (H3.4, not to be confused with testis-specific H3.4 found in animals) is very weakly expressed if at all [39]. A recent study has shown that the HHT2 expression level peaks in S phase, while the HHT3 level remains stable across the cell cycle in Tetrahymena [42]. Although, canonical H3s are strictly deposited in an RD manner, H3.3 and H3.4 can be deposited both by a transcriptionassociated RI pathway and inefficiently by an RD pathway [39].…”
Section: Introductionmentioning
confidence: 99%